2015
DOI: 10.4102/sajbm.v46i2.88
|View full text |Cite
|
Sign up to set email alerts
|

What impedes micro, small and medium firms’ growth the most in South Africa? Evidence from World Bank Enterprise Surveys

Abstract: The growth of Micro, Small and Medium Enterprises (MSMEs) is often regarded as a solution to persistent unemployment in developing countries. Studies have shown that access to finance is the most serious obstacle to MSMEs' growth. This paper investigates key obstacles to the growth of MSMEs in South Africa using the World Bank Enterprise Surveys of 2003 and 2007. Two approaches are used to determine the key obstacles. The first improves on the simple count-of-ratings method used by many researchers. The second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…Several studies in the past that use World Bank Enterprise Surveys have largely dealt with sequential multivariate regressions, especially in those studies wherein constraints need to be factored in with regards to estimation (Mthimkhulu & Aziakpono, 2015). Other notable studies have largely used instrument variable regressions with the WBES variables for the purpose of estimation the models (Jaax, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies in the past that use World Bank Enterprise Surveys have largely dealt with sequential multivariate regressions, especially in those studies wherein constraints need to be factored in with regards to estimation (Mthimkhulu & Aziakpono, 2015). Other notable studies have largely used instrument variable regressions with the WBES variables for the purpose of estimation the models (Jaax, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The spaza shop economy In 2010, South African microenterprises represented almost 8 million employment opportunities (Grundling & Kaseke, 2010), mostly for the individual owner, and were valuable sources of economic growth, job creation and poverty alleviation (Ligthelm, 2008;Mthimkhulu & Aziakpono, 2015). Spaza shops, which are a subset of microenterprises, are similarly important participants in the local economy; in 2000, 2.7% of South Africa's retail trade was from spaza shops, amounting to R7.4 billion (Ligthelm, 2005).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…There are numerous reasons that explain the failure of microenterprises and spaza shops. Issues such as low business literacy, limited access to finance and markets, lack of business skills, personal values and size of firm are widely discussed as playing an important role (Abor & Quartey, 2010;Asah, Fatoki & Rungani, 2015;Mthimkhulu & Aziakpono, 2015;Williams, 2014). It has been found in several studies that many spaza shop owners do not possess the necessary business skills or entrepreneurial expertise to be competitive (Cant & Wiid, 2013;Ligthelm, 2012;Woodward, Rolfe, Ligthelm & Guimaraes, 2011).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Participants further mentioned the following factors as main barriers to entrepreneurship: competition (30.2%), high degree of crime and corruption (26.2%), getting a business location (18.1%), insufficient networking (10.7%), inadequate skilled personnel (8.1%), inadequate managerial experience (4%) and lack of financial management skills (2%). Goldstuck (2015) and Mthimkhulu and Aziakpono (2015) surveyed the SMEs and showed that finance, competition, corruption and crime are the greatest threats to SMEs.…”
Section: Challenges Facing African Migrants In the Conduct Of Their Entrepreneurshipmentioning
confidence: 99%